Tissue Equivalents: Template Curvature Influences Cell Alignment to Create Improved Human Corneal Tissue Equivalents (Adv. Biosys. 12/2017). Issue 12 (15th December 2017) - Gouveia, Ricardo M.; Koudouna, Elena; Jester, James; Figueiredo, Francisco; Connon, Che J.
Abstract : Using the novel concept of curved tissue templating, human fibroblasts grown on dome‐shaped surfaces are capable of biofabricating corneal tissue equivalents with defined curvature and comprising highly‐aligned collagen fibrils. These robust, carrier‐free tissues presented by Che J. Connon and co‐workers in article number1700135 are subsequently retrieved via self‐release, a method involving the controlled degradation of their surface template.